2021
DOI: 10.1021/jacs.1c08153
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous Isomerization for Stereoselective Alkyne Hydrogenation to trans-Alkene Mediated by Frustrated Hydrogen Atoms

Abstract: Stereoselective production of alkenes from the alkyne hydrogenation plays a crucial role in the chemical industry. However, for heterogeneous metal catalysts, the olefins in cis-configuration are usually dominant in the products due to the most important and common Horiuti–Polanyi mechanism involved over the metal surface. In this work, through combined theoretical and experimental investigations, we demonstrate a novel isomerization mechanism mediated by the frustrated hydrogen atoms via the H2 dissociation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 55 publications
1
12
0
Order By: Relevance
“…As shown in Figure a, it can be observed from the Rh K-edge XANES spectra that the adsorption edge of a -RhS 2– x metallene is situated between the Rh foil and Rh 2 O 3 , revealing that the average valence state of Rh for a -RhS 2– x metallene is situated between the metallic Rh 0 and oxidized Rh 3+ in agreement with the XPS results . In the Rh K-edge EXAFS spectra of a -RhS 2– x metallene (Figure b), two distinct peaks in a -RhS 2– x metallene are located at 1.92 and 3.12 Å, respectively, which can be attributed to the Rh–S bond . Furthermore, Figures c and S5–S7 illustrate the Rh K-edge EXAFS experimental and fitting curves for Rh foil, Rh 2 O 3 , and a -RhS 2– x metallene.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…As shown in Figure a, it can be observed from the Rh K-edge XANES spectra that the adsorption edge of a -RhS 2– x metallene is situated between the Rh foil and Rh 2 O 3 , revealing that the average valence state of Rh for a -RhS 2– x metallene is situated between the metallic Rh 0 and oxidized Rh 3+ in agreement with the XPS results . In the Rh K-edge EXAFS spectra of a -RhS 2– x metallene (Figure b), two distinct peaks in a -RhS 2– x metallene are located at 1.92 and 3.12 Å, respectively, which can be attributed to the Rh–S bond . Furthermore, Figures c and S5–S7 illustrate the Rh K-edge EXAFS experimental and fitting curves for Rh foil, Rh 2 O 3 , and a -RhS 2– x metallene.…”
Section: Resultssupporting
confidence: 81%
“…The Rh 3d XPS spectrum reveals two distinct peaks of Rh 3d 3/2 (312.33 eV) and Rh 3d 5/2 (307.74 eV), which can be assigned to Rh 2+ . The other two small peaks situated at 313.48 and 308.88 eV can be assigned to Rh 3+ , indicating the presence of Rh–S bonds (Figure e). , In the S 2p XPS spectrum (Figure f), two distinct peaks at 163.28 and 161.92 eV correspond to S 2p 1/2 and S 2p 3/2 , respectively, originating from the presence of S 2– in the sulfide, which further proves the formation of Rh–S bonds . It is notable that the small peak at 165.7 eV reveals the presence of S–S …”
Section: Resultsmentioning
confidence: 91%
“…Selective semihydrogenation of alkynes to alkenes is an extremely important and valuable transformation and has a broad range of applications in polymer materials, pharmaceuticals, vitamins, agrochemicals, and fragrances. To date, precious Pd has been identified as the most active catalyst for alkyne semihydrogenation, and several Pd-based catalysts have been commercialized and widely used in the industry. Notwithstanding, the reaction still faces a big challenge in the precise control of selectivity due to the presence of side reactions of overhydrogenation and oligomerization. Over the past decades, great achievements have been made in the development of high-performance Pd-based catalysts with diverse strategies aiming to improve the catalytic activity and selectivity and stability as well. However, the high selectivity was usually achieved at the expense of activity due to the presence of the trade-off between the selectivity and activity caused by the linear scaling relationships between the binding energies of alkynes and alkenes. , In addition, the low Earth abundance and the high expense of noble Pd catalysts further limit the large-scale application.…”
Section: Introductionmentioning
confidence: 99%
“…As low-cost alternatives to precious metal catalysts, basemetal catalysts have been developed to achieve the E-selective semi-hydrogenation of alkynes. [18][19][20][21][22][23][24] For example, Fout and Tokmic presented a cobalt-catalyzed semi-hydrogenation of alkynes to E-alkenes using complicated N/P ligands. 25 Milstein and co-workers reported that an acridine-based PNP iron complex can catalyze the semi-hydrogenation of alkynes with high E-selectivity.…”
Section: Introductionmentioning
confidence: 99%